2002
DOI: 10.1016/s0378-2166(02)80001-7
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatics in human-computer conversations

Abstract: This paper provides a pragmatic analysis of some human-computer conversations carried out during the past six years within the context of the Loebner Prize Contest, an annual competition in which computers participate in Turing Tests. The Turing Test posits that to be granted intelligence, a computer should imitate human conversational behavior so well as to be indistinguishable from a real human being. We carried out an empirical study exploring the relationship between computers' violations of Grice's cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 12 publications
2
32
0
1
Order By: Relevance
“…Contemporary chatter bots perform very effectively in question-answer settings and similar utterance-exchange pair settings, where the contexts of the conversations are independent from one exchange to the next (Mauldin, 1994;Saygin & Ciceklib, 2002;Chakrabarti & Luger, 2012). However, they perform poorly in conversational situations where a specific context is maintained through a series of several utterance-exchange pairs.…”
Section: Conversation and Dialog Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary chatter bots perform very effectively in question-answer settings and similar utterance-exchange pair settings, where the contexts of the conversations are independent from one exchange to the next (Mauldin, 1994;Saygin & Ciceklib, 2002;Chakrabarti & Luger, 2012). However, they perform poorly in conversational situations where a specific context is maintained through a series of several utterance-exchange pairs.…”
Section: Conversation and Dialog Engineeringmentioning
confidence: 99%
“…⁄ relation: speaker's utterance is relevant to the context and the topic of the conversation ⁄ manner: speaker's utterance is direct and straightforward, without ambiguity or obfuscation Saygin and Ciceklib (2002) demonstrated that evaluating chatter bots using Grice's cooperative maxims is an effective way to compare chatter bots competing for the Loebner prize. They provide a scoring matrix, against which each artificial conversation can be graded for a specific criterion and hence offer a good potential starting point for evaluating our artificial conversations.…”
Section: Conversation Metrics Based On Grice's Maximsmentioning
confidence: 99%
“…So researchers in the field of AI have the challenge of designing a machine, endowed with functions at birth (at design), and improves with growth like a child, and learns externally (from its environment) without any further capabilities bestowed (internally) on it by its designers. An interesting statement is made by Singh and Gupta [25]: "A true AI program should be able to perceive the world around it, autonomously decide its actions and should be able to adapt itself to the changes." This reflects the requirements of a machine to pass Schweizer"s [26] Truly Total Turing Test (TTTT).…”
Section: Turing's Contribution In the Field Of Artificial Intelligencementioning
confidence: 99%
“…3) Design: To ensure the evaluation was correct, we set up the questionnaires in the following steps which can help us organize the clear comparison between human and computer performance, as in the modified Turing Test for dialogue provided in [15]:…”
Section: ) Evaluating the Controller's Performancementioning
confidence: 99%